Fitur Live Streaming dan Promosi: Apakah Berpengaruh terhadap Minat Beli pada Tiktok Shop? - Akbar, Y Rahmat; Nefrida; Putri, Anisa; Rahmadani, Auliya; Safitri, Dira Yani; Fadhillah, M Rizki (Jurnal Pustaka Manajemen (Pusat Akses Kajian Manajemen), 2025)
This study aims to analyze the influence of live streaming features and promotional activities on purchase intention on the TikTok Shop platform. The background of this research stems from the rising trend of using social media as a means of online shopping, particularly among university students who are highly connected to digital technology. A quantitative approach was employed using a survey method. Primary data were collected through questionnaires distributed to 100 respondents who actively use TikTok Shop. The analytical technique used in this study is multiple linear regression to examine the effect of each independent variable on the dependent variable. The findings indicate that the live streaming feature significantly influences students’ purchase intentions. The direct interaction enabled by live streaming enhances trust, engagement, and perceived value of the products. The study concludes that live streaming and promotional strategies are effective in increasing purchase intention among university students. Therefore, businesses on TikTok Shop are encouraged to maximize the use of live streaming features and design attractive promotions tailored to the characteristics of young consumers.